- #1

- 62

- 0

f(z) = z^2 = (x + iy)^2 = x^2 + 2ixy - y^2

u(x,y) = x^2 - y^2

v(x,y) = 2xy

- Thread starter complexnumber
- Start date

- #1

- 62

- 0

f(z) = z^2 = (x + iy)^2 = x^2 + 2ixy - y^2

u(x,y) = x^2 - y^2

v(x,y) = 2xy

- #2

Mark44

Mentor

- 34,020

- 5,674

- Last Post

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 3

- Views
- 1K

- Last Post

- Replies
- 5

- Views
- 1K

- Last Post

- Replies
- 3

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 4

- Views
- 1K

- Last Post

- Replies
- 5

- Views
- 1K

- Last Post

- Replies
- 3

- Views
- 1K

- Last Post

- Replies
- 10

- Views
- 711

- Last Post

- Replies
- 1

- Views
- 2K